Aplikasi Game Edukasi Peduli Lingkungan Berbasis Android Pada Taman Kanak-Kanak Guppi - Muzdalifah, Muzdalifah; Hidayat, Hidayat; Masrawati, Masrawati (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2023)
Environmental problems in this case, especially the waste problem, are problems that are very close to society and which until now have not been fully addressed by the relevant parties, based on this, it is one of the supporting factors for this research which is expected to be a place for early introduction to the importance of protecting the environment, as for the aim. This research is to create an Android-based environmental care educational game application at GUPPI Kindergarten and to see the results of implementing an Android-based environmental care educational game application at GUPPI Kindergarten. The process of creating an Android-based Environmental Care Educational Game Application is carried out using Unity where the process is divided into creating the design, then forming the objects in the game, then creating the scene and finally the compilation process. Based on the tests carried out, it was found that the game works well on smartphones of different types. The implementation of an Android-based environmental care educational game application carried out at Guppi Kindergarten resulted in the educational game application proving to be effective in increasing students' interest and knowledge in recognizing dry waste and wet waste.